Extraction of Soil Solution into a Microfluidic Chip - Sönke Böckmann; Igor Titov; Martina Gerken (AgriEngineering, 2021)
Collecting real-time data on physical and chemical parameters of the soil is a prerequisite for resource-efficient and environmentally sustainable agriculture. For continuous in situ measurement of soil nutrients such as nitrate or phosphate, a lab-on-chip approach combined with wireless remote readout is promising. For this purpose, the soil solution, i.e., the water in the soil with nutrients, needs to be extracted into a microfluidic chip. Here, we present a soil-solution extraction unit based on combining a porous ceramic filter with a microfluidic channel with a 12 µL volume. The microfluidic chip was fabricated from polydimethylsiloxane, had a size of 1.7 cm × 1.7 cm × 0.6 cm, and was bonded to a glass substrate. A hydrophilic aluminum oxide ceramic with approximately 37 Vol.-% porosity and an average pore size of 1 µm was integrated at the inlet. Soil water was extracted successfully from three types of soil—silt, garden soil, and sand—by creating suction with a pump at the other end of the microfluidic channel. For garden soil, the extraction rate at approximately 15 Vol.-% soil moisture was 1.4 µL/min. The amount of extracted water was investigated for 30 min pump intervals for the three soil types at different moisture levels. For garden soil and sand, water extraction started at around 10 Vol.-% soil moisture. Silt showed the highest water-holding capacity, with water extraction starting at approximately 13 Vol.-%.